2001
DOI: 10.1046/j.1469-8137.2001.00131.x
|View full text |Cite
|
Sign up to set email alerts
|

Mycorrhizal development in a low nodulating pea mutant

Abstract: Summary• E107 is a pleiotropic mutant of Pisum sativum (pea) characterized by a decreased ability to form nodules. Its colonization by the arbuscular mycorrhizal fungus Glomus aggregatum is reported, and the mycorrhizal phenotype compared with the nodulation phenotype.• Four cleared lateral roots from 21-d-old plants were chosen randomly, and their lengths scanned for any fungal structures. Colonization success was determined by counting the numbers of extraradical hyphae, and calculating epidermal entry and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 36 publications
(74 reference statements)
1
23
1
Order By: Relevance
“…Bonfante et al (2000) further studied these mutants and reported the LjSym4-1 and LjSym4-2 phenotypes. The LjSym4-1 phenotype is very similar to that of the brz pea mutant (Resendes et al 2001), except in LjSym4-1, a root surface block is not evident. The LjSym4-2 mutant exhibits a much stronger block to epidermal exit in that AM do not form because hyphae never exit the epidermis (Bonfante et al 2000).…”
Section: Interface As a Tight Checkpointsupporting
confidence: 49%
See 4 more Smart Citations
“…Bonfante et al (2000) further studied these mutants and reported the LjSym4-1 and LjSym4-2 phenotypes. The LjSym4-1 phenotype is very similar to that of the brz pea mutant (Resendes et al 2001), except in LjSym4-1, a root surface block is not evident. The LjSym4-2 mutant exhibits a much stronger block to epidermal exit in that AM do not form because hyphae never exit the epidermis (Bonfante et al 2000).…”
Section: Interface As a Tight Checkpointsupporting
confidence: 49%
“…Even in wild-type pea, numerous IT abort in the base of the epidermal cell (Guinel and LaRue 1992). Additional evidence for tight regulation of both nodulation and AM fungal colonization at this point is given by the brz mutant, in which the parallel between the two plant-microbe interactions is striking (Resendes et al 2001). In each symbiosis, there is a similar reduction in the number of infections, a block at the epidermis-cortex interface, and a few successful infections and the two phenotypes are controlled by the shoot.…”
Section: Interface As a Tight Checkpointmentioning
confidence: 93%
See 3 more Smart Citations